Identification of different Chrysoperla (Neuroptera: Chrysopidae) species collected from Ardabil province (Iran) by using claw shape - Asadi, Mohammad (Acta Biologica Szegediensis, 2022)
The family Chrysopidae has several genera of which the genus Chrysoperla is more important of them. These lacewings are beneficial insects when they have high potential for predation on harmful aphids which can be used in their biological control programs. Due to high importance of these lacewings in Ardabil province in northwest zone of Iran, identification of their species was done. By examining the collected specimens with morphological features, wing venation, male reproductive organ, and claws shape (as the best way to identify the species) fi nally 4 species were identified including Chrysoperla carnea (Stephens), Chrysoperla kolthoffi Navas, Chrysoperla lucasina Lacroix, and Chrysoperla sillemi Esben-Petresen.